Traditional and diversified crops in South Moravia (Czech Republic): Habitat preferences of common vole and mice species - Jánová, E. (Eva); Heroldová, M. (Marta); Konečný, A. (Adam); Bryja, J. (Josef) (Mammalian Biology, 2011)
Changes in the composition of crops in Central Europe (increasing areas of maize, rape and sunflower fields) have significantly influenced animal communities. We assessed the importance of these three crops for rodents and compared it with traditional crops. We confirmed the presumed differences in habitat preferences; however we rejected the hypothesis of a general increase of rodent abundance during the vegetative season in managed fields. We found that (1) maize and sunflower had no importance for common voles, but they were favored habitats for wood mice; (2) numbers of wood mice in rape decreased during the season, while abundances of common voles increased; (3) common vole populations tended to increase during the season in all suitable crops; (4) wood mice populations seemed stable in all crops; i.e. without a seasonal increase. It can be concluded that the new crop fields are only a temporal habitat for small mammals, especially granivorous species.